Activity of an nutritional supplement in lamb’s natural infection with Cryptosporidium spp. - Imre, K.,; Darabus Gh.,; Ilie M.S.,; Ionela Hotea,; Mirela Imre (Medicamentul Veterinar)
In this paper are presented the results of a test for eficiency of one nutritional suppliment as a source of electrolites and glucose in natural infection with Cryptosporidium spp. at calves. During the treatment every calf was examined three times and one time a week afther the treatment was finised. In every examination faecies were colected to have a view of oochysts elimination. It was concluded that the product tested dose not reduce the elimination of Cryptosporidium spp.oocysts, but produces a clinical improvement, reducing the diarrhea and improving the general status of the animal.